Pengaruh Kecerdasan Intelektual Dan Academic Self Efficacy Terhadap Academic Fraud Dengan Sikap Etis Mahasiswa Sebagai Variabel Moderating - Mike Nur Achmawati; Saiful Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The goal of this study is to see how intellectual intelligence affects academic cheating and how academic self-efficacy varies, with students' ethical beliefs as the limiting variable.The methodologies used in this investigation are quantitative.The survey's target audience was UPN Veteran Jawa Timur Experienced Accounting Students 2018, and the sample size was 70 people. The data analysis method is Warp PLS 7.0 Partial Least Square (PLS) software, and the sampling method is simple random sampling. The study and evaluation test results demonstrate a varying influence of intellectual intelligence on academic falsification, with a path coefficient of -0.455 and a p-value of 0.001. A path factor of -0.377 and a P-value of 0.001 were also found in variable testing of academic self-efficacy for academic fraud. The results show patf coefficients of 0.205 and P-values of 0.036 when testing the moderation variable, student ethical attitudes moderating intellectual intelligence, and academic self-report factors for academic cheating. With a P-value of 0.001, we may conclude that intellectual intelligence and academic self-efficacy factors have a negative and substantial impact on academic fraud, and that a variable in a student's ethical approach can diminish both of these variables. Keywords: intellectual intelligence, academic self-efficacy, academic fraud, student's ethical attitude